Chemistry of Pentafluorosulfanyl Derivatives and Related Analogs: From Synthesis to Applications - Kordnezhadian, Reza; Li, Bing‐Yu; Zogu, Armir; Demaerel, Joachim; De Borggraeve, Wim M.; Ismalaj, Ermal (Chemistry : a European journal, 2022)
Pentafluorosulfanyl (SF5)‐containing compounds and corresponding analogs are a highly valuable class of fluorine‐containing building blocks owing to their unique properties. The reason for that is the set of peculiar and tremendously beneficial characteristics they can impart on molecules once introduced onto them. Despite this, their application in distinct scientific fields remains modest, given the extremely harsh reaction conditions needed to access such compounds. The recent synthetic approaches via S−F, and C−SF5 bond formation as well as the use of SF5‐containing building blocks embody a “stairway‐to‐heaven” loophole in the synthesis of otherwise‐inaccessible chemical scaffolds only a few years ago. Herein, we report and evaluate the properties of the SF5 group and analogs, by summarizing synthetic methodologies available to access them as well as following applications in material science and medicinal chemistry since 2015. SF6 building blocks: This review article summarizes the recent synthetic methodology dedicated to pentafluorosulfanyl derivatives and their related analogs. The properties and up‐to‐date applications in materials sciences and medicinal chemistry of SF5‐containing compounds are also discussed here.